Dual oxidase: a novel therapeutic target in allergic disease - van der Vliet, Albert (Br J Pharmacol, 2018)
NADPH oxidases (NOXs) represent a family of enzymes that mediate regulated cellular production of reactive oxygen species (ROS) and play various functional roles in physiology. Among the NOX family, the dual oxidases DUOX1 and DUOX2 are prominently expressed in epithelial cell types at mucosal surfaces and have therefore been considered to have important roles in innate host defence pathways. Recent studies have revealed important insights into the host defence mechanisms of DUOX enzymes, which control innate immune response pathways in response to either microbial or allergic triggers. In this review, we discuss the current level of understanding with respect to the biological role(s) of DUOX enzymes and the unique role of DUOX1 in mediating innate immune responses to epithelial injury and allergens and in the development of allergic disease. These novel findings highlight DUOX1 as an attractive therapeutic target, and opportunities for the development of selective inhibitor strategies will be discussed.